PENGARUH KONFLIK KEPENTINGAN TERHADAP KONSERVATISME AKUNTANSI - Feriza Lucia Islammiyah; Indiari Afnawati; Gideon Setyo Budiwitjaksono (Pusat Riset dan Inovasi Nasional, 2023)
Research by Givoly and Hayn (2002) shows that there has been an increase in the use of accounting accounting in US companies since 1980. Conservatism is an important convention of financial reporting in accounting, hence it is called the dominant accounting principle. Conventions such as conservatism are taken into account in financial and accounting reports because business activities are constrained by tension factors. The formulation of the problem and the purpose of this research is to see how the effect of conflict of interest on accounting conservatism. The approach used in this study is a qualitative approach to literature review analysis. This data collection stage is carried out by creating an extraction formula that contains the metadata that the researcher obtained from several journal articles that have been collected and selecting items that are appropriate to the research topic regarding the analysis of the effect of conflicts of interest on accounting conservatism. The results of the research show that conflict of interest has no effect on accounting conservatism. This shows that the size of the conflict that occurs between creditors and investors regarding dividend policy will not affect the application of conservatism in the accounting for preparing the company's financial statements. The level of financial distress has a negative effect on accounting conservatism. This indicates that the higher the level of financial distress, the lower the application of accounting conservatism in the preparation of financial statements. Based on research conducted by analyzing several articles that have a topic related to the selected keywords. Some of the articles reviewed can draw conclusions that can discuss how the effect of conflicts of interest on accounting conservatism.